Effect of Ar+ beam sputtering on the magnetic anisotropy of Fe thin films deposited on the MgO(001) substrate - Syed Sheraz Ahmad; Wei He; Yong-Sheng Zhang; Jin Tang; Yan Li; Qeemat Gul; Xiang-Qun Zhang; Zhao-Hua Cheng (Results in Physics, 2017)
The Fe thin films with different initial thickness were prepared on MgO(001) substrate. Ar+ ion beam having energy of 3 keV was used to sputter the film at incident angle of 80° with respect to the film normal. Low energy electron diffraction (LEED) was employed to study the morphology and crystal quality of the film. Moreover surface magneto-optical Kerr effect (SMOKE) and anisotropic magnetoresistance (AMR) setups were used to investigate the magnetic properties of the Fe film. The values of magnetocrystalline anisotropy K1 and induced in-plane uniaxial magnetic anisotropy (UMA) Ku were derived from torque curves on the base of AMR results and found that the value of Ku was increasing with increasing the sputtering time while the intrinsic magnetocrystalline anisotropy K1 was not affected by sputtering. Similarly it is observed that the value of K1 increases with the thickness. We noted that ion beam sputtering can be used as an effective technique of manipulating the magnetic anisotropy of ultrathin magnetic films.